Inhibitors of HIV-1 Protease by Using In Situ Click Chemistry - Whiting, Matthew; Muldoon, John; Lin, Ying-Chuan; Silverman, Steven M.; Lindstrom, William; Olson, Arthur J.; Kolb, Hartmuth C.; Finn, M. G.; Sharpless, K. Barry; Elder, John H.; Fokin, Valery V. (Angewandte Chemie International Edition, 2006)
Twice poor equals potent: HIV‐1 Protease assembles its own potent inhibitor through formation of the triazole linkage from azide‐ and alkyne‐containing fragments that are themselves poor binders.